Analisis Efektivitas Pengunaan Qris untuk Transaksi Pembayaran dalam Rangka Mendorong Perkembangan Ekonomi Digital: (Studi Kasus Customer Gen Z di Bandar Lampung) - Muhammad Rasyid Ridlo; Nina Ramadhani Wulandari; Mawardi Mawardi; Ulil Albab (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The rapid adoption of QRIS (Quick Response Code Indonesian Standard) as a standardized digital payment system has transformed transactional behaviors in Indonesia, particularly among Generation Z and SMEs. This study explores the effectiveness of QRIS in driving digital transactions and its role in advancing the digital economy in Bandar Lampung, with a dual focus on Generation Z consumers and SMEs. Using a qualitative approach, data were collected through interviews with 13 Generation Z QRIS users and 3 SMEs (Jenggala, Ternatea, and Elora Studio). Findings indicate that QRIS adoption among Generation Z is driven by ease of use, speed, and practicality, though technical barriers like unstable internet connectivity and QR code scanning issues persist. For SMEs, QRIS enhances operational efficiency by reducing cash dependency (e.g., 70% of Jenggala’s transactions shifted to QRIS), automates financial management (Elora Studio), and improves customer satisfaction through faster transactions. However, challenges such as digital fraud (e.g., fake payment proofs at Jenggala) and infrastructure gaps underscore the need for systemic improvements. The study concludes that QRIS is pivotal in accelerating financial inclusion and digital economic growth, particularly when aligned with SME operational strategies and Generation Z’s tech-centric lifestyles. Recommendations include strengthening digital infrastructure, enhancing transaction security protocols, and fostering inclusive adoption across diverse business models.